2004
DOI: 10.1249/01.mss.0000147582.99810.c5
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of Casein and Whey Proteins Result in Muscle Anabolism after Resistance Exercise

Abstract: Acute ingestion of both WH and CS after exercise resulted in similar increases in muscle protein net balance, resulting in net muscle protein synthesis despite different patterns of blood amino acid responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
221
1
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(264 citation statements)
references
References 20 publications
20
221
1
10
Order By: Relevance
“…Prevention of the dephosphorylation of 4E-BP1 after a bout of RE by ingestion of whey proteins probably prevents association of the 4E-BP1 with eIF4E (43). This allows a larger increase in protein synthesis (12,28,35,43), a phenomenon previously observed after the ingestion of whey proteins (52,53). It can be speculated that whey protein alone can affect mTOR signaling TORC1 dependently and independently as the phosphorylation of 4E-BP1 from this site (Thr 37/46 ) may occur independently of TORC1 unlike the phosphorylation of p70 S6K (25,54,58).…”
Section: Discussionmentioning
confidence: 83%
“…Prevention of the dephosphorylation of 4E-BP1 after a bout of RE by ingestion of whey proteins probably prevents association of the 4E-BP1 with eIF4E (43). This allows a larger increase in protein synthesis (12,28,35,43), a phenomenon previously observed after the ingestion of whey proteins (52,53). It can be speculated that whey protein alone can affect mTOR signaling TORC1 dependently and independently as the phosphorylation of 4E-BP1 from this site (Thr 37/46 ) may occur independently of TORC1 unlike the phosphorylation of p70 S6K (25,54,58).…”
Section: Discussionmentioning
confidence: 83%
“…In summary, although several studies have analyzed the effect of whey protein supplementation on resistance training performance and outcomes [6][7][8][9], only some of them have specifically focused on resistance training individuals [10,11,3,12]. Indeed, only a few studies were focused on recreationally or well strength-trained athletes, and have reported a positive effect of whey, administered alone or combined with other nutrients, to maximize strength [13,2], lean body mass (LBM) or fat free mass (FFM) gains [2,14].…”
Section: Introductionmentioning
confidence: 99%
“…The low pH conditions in the stomach cause casein to clot, forms clumps or curds and delay gastric emptying [37]. Different from whey protein that remain soluble in the stomach, and thus are emptied rapidly, casein is converted into a solid clot, and emptied more slowly from the stomach [38]. These differences in digestive properties are likely to contribute to the different patterns of AA concentrations that have been observed after ingestion of whey or casein protein [24,38].…”
Section: Milk Composition: Protein Sub-fractions Manufacturing and Mamentioning
confidence: 99%
“…Different from whey protein that remain soluble in the stomach, and thus are emptied rapidly, casein is converted into a solid clot, and emptied more slowly from the stomach [38]. These differences in digestive properties are likely to contribute to the different patterns of AA concentrations that have been observed after ingestion of whey or casein protein [24,38]. Therefore, casein has been termed as "slow", and whey has been termed as "fast" protein [39,40].…”
Section: Milk Composition: Protein Sub-fractions Manufacturing and Mamentioning
confidence: 99%
See 1 more Smart Citation